2008
DOI: 10.1097/rhu.0b013e31817a242a
|View full text |Cite
|
Sign up to set email alerts
|

Adherence To Medications In Systemic Lupus Erythematosus

Abstract: Although lack of sufficient adherence to medications appears to be a multifactorial problem, improved communication between the healthcare provider and the patient, and less complicated medication regimens, may be especially suitable interventions to improve adherence to medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
108
6
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(129 citation statements)
references
References 26 publications
10
108
6
5
Order By: Relevance
“…This approach is supported by findings from a previous study in which the main self-reported barriers to adherence among SLE patients were examples of unintentional nonadherence (e.g., "just having forgotten" or "being busy at work") (33). In addition, suggestions by these patients on how to improve adherence all referred to actions that are related to preventing unintentional nonadherence (e.g., pill boxes or task lists).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…This approach is supported by findings from a previous study in which the main self-reported barriers to adherence among SLE patients were examples of unintentional nonadherence (e.g., "just having forgotten" or "being busy at work") (33). In addition, suggestions by these patients on how to improve adherence all referred to actions that are related to preventing unintentional nonadherence (e.g., pill boxes or task lists).…”
Section: Discussionsupporting
confidence: 59%
“…One other study has examined the relationship between age and adherence in SLE and found a nonsignificant tendency for adherent patients to be older than nonadherent patients (33). A similar effect of age on adherence has been reported in a study investigating predictors of adherence in 4 chronic illnesses (37).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…34 Another study, by Koneru et al, of non-adherence in adults of slightly younger age range (33.6±15 years), although not finding young age significant, found busy life style, lack of family or social support as key, together with poor comprehension of instructions and low educational level as significant risk factors. 35 If these few adult studies suggest that educational, cognitive and social status of SLE patients, significantly impacts on treatment adherence, it lends weight to the importance of studying NPSLE in childhood onset SLE in greater depth, where development of these skills and functions, during active childhood disease, could be potentially affected.…”
Section: Normal Cognitive Development In the Developing Child And Adomentioning
confidence: 99%